Sweden : 2017 Article IV Consultation-Press Release; Staff Report; and Statement by the Executive Director for Sweden. (IMF Staff Country Reports; Country Report, 2017)
This 2017 Article IV Consultation highlights Sweden's continued strong economic growth. Real GDP is expected to rise by 3.1 percent in 2017, driven by both domestic demand and exports growing at a similar pace. Robust job creation of over 2 percent has lowered unemployment to 6.8 percent, or just 4.5 percent excluding full-time students. Housing price increases have moderated somewhat in 2017, to 7 percent year over year in September. Aided by large increases in new dwelling construction, signs of further market cooling have emerged in recent months. Household credit growth has also eased somewhat in 2017. Unexpectedly, strong government revenues in 2016 have carried forward into 2017, with the general government fiscal surplus projected at 1 percent of GDP.